The State Railway of Thailand Line Capacity Evaluation using UIC 406 Method (Section Hua Ta Khe Station to Cha Choeng Sao Junction) - Jaikaew, Niti; Sirikijpanichkul, Ackchai (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 25, 2020)
This paper evaluates the State Railway of Thailand (SRT) freight line capacity from Hua Ta Khe Station to Cha Choeng Sao Junction using the International Union of Railway’s methodology (UIC 406). The approach is to compress the timetable, calculate the capacity consumption and evaluate the possible additional train paths on a macroscopic level. Two Line Sections (LS) is defined for this Train Path Line Section (TPLS). The analysis shows the 100% capacity consumption for the whole TPLS but 49% and 55% for each LS (using 43% additional time). The new timetable is proposed by dividing the operation into 2 sections. 18 container freight trains and 2 commodity freight trains are added. The line section capacity consumption after the evaluation process is 82% and 91% respectively.